2014 SID Display Industry Award Winners. Issue 3 (1st May 2014) - Donelan, Jenny
Abstract : Once again, The Society for Information Display's Display Industry Awards Committee has selected six award winners that have advanced the state of the art of display products and technology in the categories of Display of the Year, Display Component of the Year, and Display Application of the Year.